India Since Independence - Chandra Bipin; Mukherjee Mridula; Mukherjee Aditya (Gurgaon Penguin Books, 2008)
The story of the forging of India, the world$1 (Bs largest democracy, is a rich and inspiring one. This volume, a sequel to the best-selling India$1 (Bs Struggle for Independence, analyses the challenges India has faced and the successes it has achieved in the light of its colonial legacy and century-long struggle for freedom. It covers the framing of the Constitution and the evolution of the Nehruvian political and economic agenda and basics of foreign policy; the consolidation of the nation and contentious issues like party politics in the Centre and the states, the Punjab problem, and anti-caste politics and untouchability. These, along with objective assessments of Jawaharlal Nehru, Indira Gandhi, Jayaprakash Narayan, Lal Bahadur Shastri, Rajiv Gandhi, Vishwanath Pratap Singh, Atal Bihari Vajpayee and Manmohan Singh, constitute a remarkable overview of a nation on the move.s
Includes bibliographical references and index
Keywords: History -- India; Indian History; India -- History; Independence -- India